Practical philosophy and moral education: beyond objetivisms and subjetisms morals - Gómez Navarro, Ángel (2012)
The present paper promotes a new moral education that seeks to overcome the moral subjectivisms and objectivisms morals, and proposes the need to form the moral autonomy of the person counteracting all kinds of moral heteronomy in our society. As a theoretical reference, start point is the Kant’s moral philosophy and educational vision of one of the fathers of the social sciences, Emile Durkheim, to end in the practical philosophy of Jürgen Habermas, previous analysisabout conception of moral development proposed by the cognitive-evolutionary psychology of Jean Piaget and Lawrence Kohlberg.